2016
DOI: 10.1016/j.aninu.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of infusing milk precursors into the artery on rumen fermentation in lactating cows

Abstract: This experiment was conducted to investigate the effects of infusing milk precursors into the external pudic artery on rumen fermentation in lactating dairy cows. Eight multiparous Holstein cows were randomly assigned to Group A (experimental group) and Group B (control group) with 4 cows each. A 2 × 4 complex factor crossover design was used. Cows in Group A were fed corn straw as the only roughage, and cows in Group B were fed mixed roughage. The experiment was divided into two periods. In the first period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…These results are inconsistent with the increased values of serum protein and VFAs in the HW group. A few reports have found that ruminal pH is essential to the digestibility of ADF and NDF [ 26 , 27 ]. Therefore, the rumen fluid pH, which was not significantly different in this experiment, might be the reason for the lack of difference in the digestibility of ADF and NDF.…”
Section: Discussionmentioning
confidence: 99%
“…These results are inconsistent with the increased values of serum protein and VFAs in the HW group. A few reports have found that ruminal pH is essential to the digestibility of ADF and NDF [ 26 , 27 ]. Therefore, the rumen fluid pH, which was not significantly different in this experiment, might be the reason for the lack of difference in the digestibility of ADF and NDF.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of rumen microbial proteins is directly related to nitrogen metabolism in the rumen ( Li et al, 2019 ). Appropriate energy and protein levels in the rumen are more conducive to the growth and reproduction of rumen microorganisms and increase the utilization of feed protein by microorganisms ( Wang et al, 2016 ). In the arginine and proline metabolism pathway, arginine is degraded by arginase to ornithine, which is metabolized to produce γ -aminobuytric acid (GABA).…”
Section: Discussionmentioning
confidence: 99%
“…The differential Prevotella content can alter the carbohydrate, energy, lipid, and amino acid metabolism, causing an increase in acetate, butyrate, and propionate in the HPF group. Acetate and butyrate are milk fat precursors, while propionate is the precursor of milk protein [ 63 , 64 ]. The HPF group microbiome can effectively digest the feed ingredients to degrade them into pyruvate, finally generating more VFA.…”
Section: Discussionmentioning
confidence: 99%